Challenges of Social Housing Policies, Migration and Decentralization. Case Study in Tacna City - Mamani, Delia (2020)
The problem of social housing during the process of decentralization that took place in the City of Tacna has endured a series of administrative difficulties in relation to various institutional factors as well as the appearance of new actors in the decentralization process of the year 2002. In the First Section we explain Social Housing Policies, followed by the development of the key concepts to finally present the results of the research based on a qualitative strategy, obtaining direct information from stakeholders. Thus, we argue that the problem of social housing has endured a series of administrative difficulties in relation to institutional factors from the process of decentralization and migration since the early years of the twenty-first century.